Visualization of soft tissues by highly sensitive X-ray crystal analyzer-based multi diffraction enhanced imaging. (4th August 2015) - Wu, Yanlin; Sunaguchi, Naoki; Lin, Xiaojie; Wang, Yongting; Yuasa, Tetsuya; Hirano, Keiichi; Hyodo, Kazuyuki
Abstract: In this paper, we propose a novel multi diffraction enhanced imaging (MDEI) technique to improve contrast resolution owning to the sharp rise of the reflectivity curve and high contrast-to-noise ratio (CNR). MDEI is derived from the diffraction enhanced imaging (DEI) technique. Here, DEI and MDEI phase contrast tomograms are compared. The results show that MDEI offers higher contrast resolution, while DEI has higher spatial resolution. This study provided indications for developments and applications of X-ray crystal analyzer-based imaging to obtain a higher contrast resolution.